Greeting and to enquire after’s well-being” in Turkic (Uzbek, Karakalpak, Turkmen) languages (Eurasian Journal of Learning and Academic Teaching, 2022)
Although greetings or to enquire after’s well-being are pronounced differently in the speech of each nation, the content of the lexeme, that is, the semantics, has the same meaning in many places. It is inextricably linked to religious beliefs and convictions. Practicing a language while engaging in activities is a great complement to the conversation